Does Post-/Long-COVID-19 Affect Renal Stiffness without Causing any Chronic Systemic Disorders? - Çitil, Serdal; Aksu, Yusuf (Current Medical Imaging, 2024)
Background In the last few years, coronavirus disease 2019 (COVID-19) has changed human lifestyle, behavior, and perception of life. This disease is caused by severe acute respiratory syndrome coronavirus 2 (SARS-COV-2). In the literature, there are limited studies about the late renal effects of COVID-19 that reflect the systemic involvement of this disease. Aim In the present study, we aimed to compare sonoelastographic changes in both kidneys between patients who had totally recovered from COVID-19 and healthy individuals using strain wave elastography (SWE). Methods This study was conducted between June 2021 and May 2022 in Kahramanmaraş City Hospital Department of Radiology. File and archive records were retrospectively evaluated. Basic demographic, laboratory, and renal ultrasonography (USG) and sonoelastographic findings were screened and noted. Two groups were defined to compare sonoelastographic findings. Post-/long-COVID-19 group had 92 post-long COVID-19 patients, and the comparator group comprised healthy individuals”. Both groups’ demographic, laboratory, and ultrasound-elastographic findings were assessed. Results The post-long COVID-19 group had a higher renal elastographic value than the comparator group (1.52 [0.77–2.3] vs. 0.96 [0.54–1.54], p<0.001). There were no statistically significant differences between the two groups in terms of age (p=0.063), gender (p=0.654), or body mass index (BMI) (p=0.725), however, there was a significant difference observed between the two groups in the renal strain ratio (RSR). According to an receiver operating characteristic curve (ROC) analysis, an RSR cutoff of >1.66 predicted post-long COVID-19 with 44.9% sensitivity and 81.9% specificity. (AUC=0.655, p<0.001). A separate ROC analysis was performed to predict post-long COVID-19 with a BMI cutoff of <33.52, kg/m2 sensitivity of 92.4% and specificity of 17% (AUC=0.655, p<0.001). Conclusion We demonstrated that renal parenchymal stiffness increases with SWE in post-long COVID-19 patients.
Keywords: Ultrasound